A NEGOTIATION MODEL FOR FREEZING MASTER PRODUCTION SCHEDULE NERVOUSNESS IN SUPPLY CHAINS TO MINIMIZE THE PREFERENCE DISTANCE - Aisyati, Azizah
This paper proposes a negotiation model that can be used to determine the frozen interval to overcome master production schedule instability on the part of both the manufacturer and supplier. To maintain profit margin, the manufacturer prefers to minimise the frozen interval to cope with changes in demand. In contrast, the supplier prefers to maximise the frozen interval to smooth the production level. The length of the frozen interval will affect the pricing policies of both parties. This paper therefore proposes a two-stage model based on a linear function representing the preference of each party. In the first stage, Model F is used to determine the frozen interval offered by both the manufacturer and supplier, while in the second stage, Model P is applied to find the price of the component, taking into consideration the upper and lower limits on the profit margin. To allow the two parties to reach an agreement, a two-stage negotiation model is proposed that can determine the minimum preference distance between the proposal and counterproposal made by the manufacturer and supplier, respectively. We propose three scenarios that can be used to overcome negotiation failure by each party. Numerical examples with a two-level product structure are given to show that the negotiation agreement can satisfy both parties. The parameters that affect the negotiation agreement are the lead time, the holding costs to the manufacturer and supplier, and the average cost of increasing one unit of planned production.